The Comparison between the Strength of Stabilized Cement Clay Columns and Remolded Cement Clay Samples - Mohamed Ahmed, Hafez; N., Sidek; Zakaria, Che Muda; Nur Irfah, .; Mohamad Shakri, Shariff (INTI International University, 2023)
The addition of a stabilizer i.e. cement or lime changes the clay particles in the clayey soils. Instead of the plate-like or flaky shape of particles, the formation of CSH or CAH cluster which has spider or hairy cluster shapes (under scanning electron microscope) has created bonding which increased the shear strength of the stabilized soils significantly. According to BS 1924, in preparing the soil samples for unconfined compression, the stabilized soils need to be compacted to a certain degree of compaction utilizing dynamic compaction. The author suggested that this dynamic compaction, without any measurement regarding what was the energy amount being imposed on the stabilized soil samples, might damage the CSH clusters or CSH matrix gel thus resulting in non-reliable results on the strength of the laboratory-prepared specimens. This result also does not resemble the strength developed in cement columns or lime columns in the field. The study is divided into three major stages. The first was the preparation of samples for UCT based on BS 1924, which were compacted using static packing pressure (SPp). Secondly is the development of a small-scale physical model to study the undrained shear strength of the stabilized kaolinite. Thirdly, the preparation of UCT samples compacted to a pre-determined packing pressure (PPp). Pre-determined packing pressure is 50% of the (SPp). It was found that reducing 50% of the (SPp) has reduced the strength of samples significantly. The strength of the samples compacted to 100% SPp is approximately ten times higher than that of the uncompacted cement column strength after 56 days of curing. The ionic conductivity trend shows that as the strength increases, the conductivity value decreases. This finding has led to the conclusion that electric or ionic conductivity tests can be applied as supporting tests in predicting the strength development in cement-stabilized kaolinite.